Zero-till drill for the establishment of mungbean and comparison of its performance with the conventional method - Islam, Md. Hamidul; Ansari, Md. Shamshad; Nandi, Rajesh; Hossain, Md. Mosharraf; Haquee, Md. Enamul (Journal of the Bangladesh Agricultural University, 2020)
The conventional method of mungbean (Vigna radiata) cultivation is direct broadcasting involves land preparation and seeding which is laborious, time-consuming and cost-intensive. Conservation agriculture-based technologies are becoming increasingly popular among the farmers due to having early planting scope, the minimum cost of production, improving soil health and sustainable environment. This study was conducted to evaluate the performance of a power tiller operated zerotill drill for the adoption in mungbean cultivation. Overall performance was evaluated based on seed rate, number of plants per unit area, number of pods per plant, number of seeds per pod and grain yield, net saving and benefit-cost ratio, and compared with the conventional method. Results showed that average seed rate was 30.0 kg/ha and 35.5 kg/ha for zero tillage and conventional method respectively, which indicates that 5.5 kg of seed per ha was saved with zero tillage system. Besides, zero tillage system could maintain a uniform depth of planting with better seed-soil contact. The average number of plants, pods per plant, seed per pods and yield per hectare were higher in zero tillage system compared to the conventional method. Mungbean yield under zero tillage system was 30.4% higher than the conventional method. Furthermore, from an economic viewpoint, zero tillage system is suitable for mungbean cultivation because it could save the production cost by 20.9% and increased net saving by 60.9% than the conventional method. Furthermore, a higher benefit-cost ratio was obtained from the zero tillage system (BCR = 3.2) than the conventional system (BCR = 1.6) which indicates that zero tillage system is profitable than the conventional method. J Bangladesh Agril Univ 18(2): 509–515, 2020 https://doi.org/10.5455/JBAU.81033